THE INFLUENCE OF WORK STRESS AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF BALAI PUSAT PENDIDIKAN DAN PELATIHAN (PUSDIKLAT) PT. KAI DURING THE COVID-19 PANDEMIC - Destyanti, Fira; Devi, Eunike; Girsang, Yulis; Pribadi, Ridda; Gustiawan, Dimas; Marinda, Vina S. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Human resources are the most important element of the company. Since the covid- 19 pandemic, the level of work stress experienced by employees has increased due to changes in the work environment that also have an impact on decreasing employee work motivation levels. This research aims to determine the influence of work stress and work motivation on employee performance at Balai Pusat Pendidikan dan Pelatihan (PUSDIKLAT) PT. KAI during the Covid-19 pandemic. This quantitative research approach with this type of explanatory research and a structured survey method through questionnaires. Sampling technique using census sampling technique with the number of samples as many as 50 employees who work at Balai Pusat Pendidikan dan Pelatihan (PUSDIKLAT) PT. KAI. The results of the t-testobtained that work stress (X1) did not have a significant effect on employee performance (Y) with a t-count value smaller than the t-table, which is 1,318 < 2,012. As for work motivation (X2) has a significant effect on employee performance (Y) with t-calculate > t-table, namely, 7,629 > 2,012. For model feasibility tests, work stress (X1) and work motivation (X2) had a significant effect on employee performance (Y) with f- count > f-tables, which were 32,664 > 3.20. In addition, the large influence of both independent variables on employee performance was 58.2%.